Socioeconomic status, antidepressant use, and return to work after disability due to common mental disorders - Helena Leppänen; Olli Kampman; Reija Autio; Antti Tanskanen; Heidi Taipale; Tino Karolaakso; Päivi Rissanen; Turkka Näppilä; Sami Pirkola (European Psychiatry)
Abstract Background Common mental disorders (CMDs) are significant causes of work disability. Low socioeconomic status (SES) is a known risk factor for CMDs and work disability, one possible reason being poorer treatment adherence. We aimed to study the realization of pharmacological treatment and antidepressant adherence in patients with CMDs 3 years before and 3 years after being granted a disability pension (DP) and the role of SES in this. We also studied whether antidepressant adherence is associated with return to work (RTW) after a temporary DP.